Carbon quantum dot optimized furfuryl alcohol modified material and preparation method thereof

By using surface ion-modified carbon quantum dot catalytic furfuryl alcohol modification technology, the problems of deterioration of toughness and blackening of wood modified materials are solved, and the overall optimization of wood performance and multi-effect catalytic effect are achieved.

CN119635780AActive Publication Date: 2025-03-18BEIJING FORESTRY UNIVERSITY

Patent Information

Application Number
CN202510029127.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

In the existing wood furfurol modification technology, the problems of deterioration of the toughness of the modified material and the blackening of the material color have not been effectively solved, and traditional catalysts also have problems of brittleness and single function.

Method used

The surface ion modified carbon quantum dots are used as catalysts to treat the wood by vacuum pressurized impregnation method, and aged at room temperature and cured by heating to form a carbon quantum dot-optimized furfurol modified material.

Benefits of technology

It significantly improves the dimensional stability, compressive strength, biodegradability and toughness of the wood, solves the problem of blackening of the material color, and achieves the overall performance optimization of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635780A_ABST
    Figure CN119635780A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wood modification, and particularly relates to a carbon quantum dot optimized furfuryl alcohol modified material and a preparation method thereof. The preparation method comprises the following steps that wood is treated with carbon quantum dot / furfuryl alcohol modified liquid through a vacuum pressurization impregnation method, then the wood is wrapped with a high-temperature-resistant waterproof material, and aging is conducted at the room temperature. And finally, the wood is heated and cured, and therefore the carbon quantum dot optimized furfuryl alcohol modified material is obtained. According to the carbon quantum dot / furfuryl alcohol modified liquid, the carbon quantum dots serve as a catalyst to catalyze curing of furfuryl alcohol in wood and also serve as a wood modifier to endow the wood with excellent corrosion resistance, and multiple effects are achieved through one agent. According to the carbon quantum dot optimized furfuryl alcohol modified material, the problem that the toughness of the furfuryl alcohol modified material is reduced is solved, overall balance and optimization of the dimensional stability, the strength, the toughness and the biological degradation resistance of wood are achieved, and the problem that the material color of the modified material is blackened is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood modification, and particularly relates to a carbon quantum dot optimized furfuryl alcohol modified material and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As a renewable and recyclable green ecological material, wood is widely used in various fields such as construction, furniture, and decoration due to its excellent physical and mechanical properties and unique environmental characteristics, such as high strength-to-weight ratio, easy processing, and beautiful texture. However, there are a large number of hygroscopic groups in the main components of wood, which leads to its unstable size, deformation and cracking, and causes microbial deterioration such as mildew and decay. Therefore, in order to avoid these problems, wood needs to be modified.

[0004] Furfuryl alcohol modification of wood is to use furfuryl alcohol as a modifier, which is compounded with a catalyst to impregnate and fill the cell cavity and cell wall of the wood, and solidify into furfuryl alcohol resin in the wood after heating, thereby improving the performance of the wood. The furfuryl alcohol modification process is simple, and the dimensional stability, compressive strength along the grain and resistance to biological degradation are significantly improved after modification. In addition, the modifier is made from agricultural residues, has a wide source, is low in toxicity and environmentally friendly, so it is valued by the industry and has been commercialized in some European countries and the United States. However, due to the brittleness of the furfuryl alcohol resin itself and the use of acidic catalysts and heating conditions during the modification process, the toughness of the modified material is greatly reduced. When the weight gain rate of the furfuryl alcohol modified material reaches 70%, the impact toughness of the wood can be reduced by 57%. At present, the method of removing lignin from the wood and introducing flexible polymers can alleviate the decrease in toughness of furfuryl alcohol modified materials to a certain extent, but the effect is not ideal, and the process is complicated and difficult to industrialize. So far, no research has been conducted to improve the toughness of furfuryl alcohol modified materials by designing catalysts. In addition, traditional catalysts such as sulfuric acid and maleic anhydride have violent reactions and single functions, which restricts the promotion and application of furfuryl alcohol modification technology in the wood modification industry. Therefore, designing a mild catalytic and multi-effect catalyst to optimize the furfuryl alcohol modification technology of wood has important practical application value.

[0005] Carbon quantum dots (CQDs) are a type of zero-dimensional carbon nanomaterial, mainly composed of C, H and O elements. It has the advantages of small particle size and large specific surface area. It has many groups on the surface, which can provide abundant central active sites for catalysis. It has excellent electron transfer ability and can act as an electron acceptor and electron donor. In addition, CQDs have good hydrophilicity, low toxicity, a wide range of synthetic materials and simple synthesis methods, making it an ideal catalyst. Therefore, this study used carbon quantum dots to catalyze the curing of furfuryl alcohol monomer, which significantly improved the dimensional stability, compressive strength and resistance to biological degradation of wood, improved the problem of toughness reduction, achieved the overall balance and optimization of dimensional stability, strength, toughness and resistance to biological degradation, and solved the problem of blackening of wood color. Summary of the invention

[0006] The purpose of the present invention is to solve the problem of decreased toughness of furfuryl alcohol modified materials, to achieve overall balance and optimization of wood dimensional stability, strength, toughness and resistance to biological degradation by designing a new catalyst, and to solve the problem of blackening of wood color, and to provide a carbon quantum dot optimized furfuryl alcohol modified material and a preparation method thereof.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions:

[0008] In the first aspect, the present application proposes a method for preparing a carbon quantum dot optimized furfuryl alcohol modified material, wherein the carbon quantum dot / furfuryl alcohol modified liquid is treated with wood by vacuum pressure impregnation, and then the wood is wrapped with a high temperature resistant and waterproof material and aged at room temperature so that the modifier can better enter the wood cell wall. Then, the wood is placed in a drying oven or a drying kiln for heating and curing, thereby obtaining a carbon quantum dot optimized furfuryl alcohol modified material.

[0009] Furthermore, the carbon quantum dots are surface ion-modified carbon quantum dots.

[0010] Furthermore, the method for obtaining the carbon quantum dot / furfuryl alcohol modified solution comprises:

[0011] The carbon quantum dots, furfuryl alcohol and water are mixed to obtain the carbon quantum dots / furfuryl alcohol modified solution.

[0012] Furthermore, in terms of mass percentage, the carbon quantum dot concentration is 0.5-5%, the furfuryl alcohol concentration is 10-70%, and the water concentration is 25-89.5%.

[0013] The vacuum pressure impregnation method is to first perform vacuum treatment for 30 to 120 minutes at a vacuum degree of -0.05 to -0.1 MPa, then introduce the carbon quantum dot / furfuryl alcohol modification solution, and then perform pressure treatment for 60 to 180 minutes at a pressure of 0 to 2 MPa.

[0014] Furthermore, the high temperature resistant and waterproof material is tin foil and / or silicone oil paper, and the room temperature aging time is 12 to 72 hours.

[0015] The heating and curing treatment is firstly treated at 60-80° C. for 1-5 hours, and then treated at 100-120° C. for 5-24 hours. Finally, the high temperature resistant waterproof material is removed, and the mixture is dried at 40-80° C. to a constant weight.

[0016] In a second aspect, the present application proposes a wood material prepared by the above-mentioned method for preparing the carbon quantum dot-optimized furfuryl alcohol-modified material.

[0017] The beneficial effects of the present invention are:

[0018] In the carbon quantum dot / furfuryl alcohol modified liquid of the present invention, the carbon quantum dots act not only as a catalyst to catalyze the solidification of furfuryl alcohol in wood, but also as a wood modifier to impart excellent corrosion resistance to the wood, thus achieving multiple effects with one dose.

[0019] The carbon quantum dot-optimized furfuryl alcohol modified material of the present invention solves the problem of decreased toughness of the furfuryl alcohol modified material, achieves overall balance and optimization of the dimensional stability, strength, toughness and resistance to biological degradation of the wood, and solves the problem of blackening of the modified material.

[0020] The carbon quantum dots of the present invention are simple to prepare, have no solid byproducts, are short in time and low in cost, and can be widely promoted and applied. The carbon quantum dots of the present invention are ion-modified, and the surface contains abundant hydroxyl groups, carboxyl groups and ions, which can play the role of acid catalysis and hydrogen bond catalysis, and have good catalytic furfuryl alcohol monomer curing and antibacterial performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the material colors of Comparative Examples 1, 3 and Example 2.

[0022] Figure 2 It is a schematic diagram of the bending strength and elastic modulus of Comparative Examples 1, 2 and Example 1.

[0023] Figure 3 Schematic diagram of the compressive strength along the grain of Comparative Examples 1, 2 and Example 1.

[0024] Figure 4 It is a schematic diagram of the impact toughness of Comparative Examples 1, 3 and Example 2.

[0025] Figure 5 It is a schematic diagram of the corrosion resistance of Comparative Examples 1, 3 and Example 2.

[0026] Figure 6 It is a schematic diagram of the dimensional stability of Comparative Example 3 and Example 2. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The embodiments provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following embodiments.

[0028] In the following examples, the preparation of the carbon quantum dot modified solution, the carbon quantum dots can be prepared by the method in the prior art, for example, "an ion-based carbon quantum dot and its application in resin curing" proposed in the Chinese patent application with publication number CN118956387A. Polybasic organic acid and fluoroborate are used as raw materials, and after being fully dissolved by ultrasound, they are placed in a microwave oven and heated for 3 to 10 minutes to obtain surface ion-modified carbon quantum dots. Then, the carbon quantum dots, furfuryl alcohol and water are mixed in a certain proportion to obtain a carbon quantum dot / furfuryl alcohol modified solution.

[0029] Example 1

[0030] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 4 parts of oxalic acid and 1 part of sodium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 5 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 1.25%, the furfuryl alcohol concentration was 15%, and a uniform yellow clear solution was obtained;

[0031] Wood processing and characterization: Populus cathayana was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0032] Vacuum pressure impregnation of wood: vacuum treatment for 45 minutes under vacuum degree -0.05MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 90 minutes under pressure of 0.5MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with tin foil, and age it at room temperature for 48 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 80°C for 2 hours, and then at 105°C for 10 hours. Remove the aluminum foil and finally dry it at 80°C to constant weight to obtain carbon quantum dot optimized furfuryl alcohol modified material.

[0033] Example 2

[0034] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 3 parts of citric acid and 2 parts of sodium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 8 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 2.5%, the furfuryl alcohol concentration was 30%, and a uniform yellow clear solution was obtained.

[0035] Wood processing and characterization: Radiata pine was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0036] Vacuum pressure impregnation of wood: vacuum treatment for 60 minutes under vacuum degree -0.1MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 120 minutes under pressure of 0.8MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with tin foil, and age it at room temperature for 36 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 60°C for 2 hours, and then at 110°C for 10 hours. Remove the tin foil and finally dry it at 60°C to constant weight to obtain carbon quantum dot optimized furfuryl alcohol modified material.

[0037] Example 3

[0038] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 5 parts of citric acid and 2 parts of ammonium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 12 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 0.5%, the furfuryl alcohol concentration was 10%, and a uniform yellow clear solution was obtained.

[0039] Wood processing and characterization: Pinus sylvestris was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0040] Vacuum pressure impregnation of wood: vacuum treatment for 30 minutes under vacuum degree -0.08MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 60 minutes under pressure of 0.3MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with silicone oil paper, and age it at room temperature for 72 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 60°C for 2 hours, and then at 120°C for 15 hours. Remove the silicone oil paper and finally dry it at 40°C to a constant weight to obtain a carbon quantum dot optimized furfuryl alcohol modified material.

[0041] Example 4

[0042] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 2 parts of oxalic acid and 1 part of ammonium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 8 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 5%, the furfuryl alcohol concentration was 70%, and a uniform yellow clear solution was obtained.

[0043] Wood processing and characterization: Eucalyptus was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0044] Vacuum pressure impregnation of wood: vacuum treatment for 120 minutes under vacuum degree -0.1MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 180 minutes under pressure of 1.5MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with tin foil, and age it at room temperature for 72 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 80°C for 5 hours, and then at 110°C for 20 hours. Remove the tin foil and finally dry it at 50°C to constant weight to obtain carbon quantum dot optimized furfuryl alcohol modified material.

[0045] Example 5

[0046] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 2 parts of oxalic acid and 1 part of ammonium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 10 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 3%, the furfuryl alcohol concentration was 50%, and a uniform yellow clear solution was obtained.

[0047] Wood processing and characterization: Populus cathayana was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0048] Vacuum pressure impregnation of wood: vacuum treatment for 100 minutes under vacuum degree -0.08MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 160 minutes under pressure of 1.2MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with silicone oil paper, and age it at room temperature for 60 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 70°C for 4 hours, and then at 120°C for 15 hours. Remove the silicone oil paper and finally dry it at 70°C to a constant weight to obtain a carbon quantum dot optimized furfuryl alcohol modified material.

[0049] Example 6

[0050] Preparation of carbon quantum dots / furfuryl alcohol modified solution: 4 parts of oxalic acid and 1 part of ammonium fluoroborate were used as raw materials, and after being fully dissolved by ultrasound, they were placed in a microwave oven and heated for 10 minutes to obtain surface ion-modified carbon quantum dots. According to the mass percentage, a glass rod was used to stir and prepare the carbon quantum dots / furfuryl alcohol modified solution: the carbon quantum dots concentration was 1.5%, the furfuryl alcohol concentration was 20%, and a uniform yellow clear solution was obtained.

[0051] Wood processing and characterization: Radiata pine was selected and processed into test materials with dimensions of 20 mm (axial) × 20 mm (tangential) × 20 mm (radial), 80 mm (axial) × 10 mm (tangential) × 4 mm (radial), and 30 mm (axial) × 20 mm (tangential) × 20 mm (radial);

[0052] Vacuum pressure impregnation of wood: vacuum treatment for 30 minutes under vacuum degree -0.1MPa, then introduce carbon quantum dot / furfuryl alcohol modification liquid, and then pressurize for 60 minutes under pressure of 1.5MPa. After impregnation, wipe off the excess modifier on the surface, wrap the wood with silicone oil paper, and age it at room temperature for 12 hours to allow the modifier to better enter the wood cell wall. Then, place the wood in a drying oven for heating and curing, first at 80°C for 4 hours, and then at 100°C for 9 hours. Remove the silicone oil paper and finally dry it at 50°C to constant weight to obtain carbon quantum dot optimized furfuryl alcohol modified material.

[0053] It should be noted that for the processing and characterization of wood, wood without bark can be selected. If it is a heartwood species, try to choose the sapwood part and saw the wood into test pieces of a certain size. You can choose broad-leaved wood, such as poplar, oak, eucalyptus, etc., and also coniferous wood, such as fir, radiata pine, Scotch pine, etc.

[0054] In the above embodiment, when the wood is vacuum-pressurized impregnated, the carbon quantum dot / furfuryl alcohol modification liquid can be used to treat the wood by a vacuum-pressurized impregnation method. After impregnation, wipe the excess modifier on the surface with a paper towel. And age at room temperature so that the modifier can better enter the cell wall of the wood. Then, the wood is placed in a drying oven for heating and curing treatment to obtain a carbon quantum dot-optimized furfuryl alcohol modified material. The physical and mechanical properties of the modified material include improved impact toughness, flexural strength and elastic modulus, compressive strength, dimensional stability and corrosion resistance.

[0055] Comparative Example 1

[0056] Untreated wood was dried at 103°C to constant weight, and physical and mechanical test specimens of the above dimensions were prepared.

[0057] Comparative Example 2

[0058] By mass percentage, the concentration of maleic anhydride was 1.25%, and the concentration of furfuryl alcohol was 15%, and a uniform light yellow clear solution was obtained; then, vacuum pressure impregnation of wood was performed in the same manner as in Example 1.

[0059] Comparative Example 3

[0060] By mass percentage, the concentration of maleic anhydride was 2.5%, and the concentration of furfuryl alcohol was 30%, and a uniform light yellow clear solution was obtained; then, vacuum pressure impregnation of wood was performed in the manner of Example 2.

[0061] After modification, the weight gain rate, volume increase rate and density change rate of Examples 1, 2 and Comparative Examples 2, 3 are shown in Table 1. It can be seen from the table that the weight gain rate and volume increase rate of Example 2 using carbon quantum dots as catalyst are greater than those of Comparative Example 3 using traditional catalysts, and the density change rate shows that the density changes of the two are basically the same. Similarly, Example 1 and Comparative Example 2 also show similar changes. This shows that the carbon quantum dot catalyst can successfully solidify furfuryl alcohol inside the wood and has a strong swelling effect on the cell wall. Table 1 Weight gain rate, volume increase rate and density change rate of Examples 1, 2 and Comparative Examples 2, 3

[0062] Figure 1 Schematic diagram of material color of comparative examples 1, 3 and embodiment 2. Figure 1It can be seen that comparative example 2 is black and darker in color, while example 2 using carbon quantum dots as a catalyst is brown, which improves the problem of the black color of the furfuryl alcohol-modified material.

[0063] Figure 2 Schematic diagram of the bending strength and elastic modulus of Comparative Examples 1, 2 and Example 1. Figure 2 It can be seen that the flexural strength and elastic modulus of Example 1 using carbon quantum dots as catalyst are greater than those of Comparative Example 2.

[0064] Figure 3 Schematic diagram of the compressive strength along the grain of Comparative Examples 1, 2 and Example 1. Figure 3 It can be seen that the compressive strength along the grain of Example 1 using carbon quantum dots as a catalyst is greater than that of Comparative Example 2.

[0065] Figure 4 It is a schematic diagram of the impact toughness of comparative examples 1, 3 and embodiment 2. Figure 4 It can be seen that the toughness of comparative example 3 decreased by 35%, while the toughness of example 2 using carbon quantum dots as catalyst increased by 38% compared with comparative example 3, and even exceeded the toughness of the untreated material, which is mainly due to the interaction between carbon quantum dots and wood.

[0066] Figure 5 It is a schematic diagram of the corrosion resistance of comparative examples 1, 3 and embodiment 2. Figure 5 It can be seen that comparative example 3 has a certain corrosion resistance, while example 2 using carbon quantum dots as catalyst has excellent corrosion resistance and achieves a sterilization effect.

[0067] Figure 6 It is a schematic diagram of the dimensional stability of comparative example 3 and embodiment 2. Figure 6 It can be seen that compared with Comparative Example 2, the anti-swelling rate of Example 2 using carbon quantum dots as catalyst increased by 22%, and the anti-swelling rate reached 80%, which indicates that the carbon quantum dot optimized furfuryl alcohol modified material has good dimensional stability.

Claims

1. A method for preparing a carbon quantum dot optimized furfuryl alcohol modified material, characterized in that: The carbon quantum dot / furfuryl alcohol modified liquid is treated with wood by vacuum pressure impregnation, and then the wood is wrapped with a high temperature resistant waterproof material and aged at room temperature. Finally, the wood is placed in a drying oven or a drying kiln for heating and curing to obtain a carbon quantum dot optimized furfuryl alcohol modified material.

2. A method for preparing a carbon quantum dot optimized furfuryl alcohol modified material as claimed in claim 1, characterized in that: The carbon quantum dots are surface ion-modified carbon quantum dots.

3. A method for preparing a carbon quantum dot optimized furfuryl alcohol modified material as claimed in claim 2, characterized in that: The method for obtaining the carbon quantum dot / furfuryl alcohol modified liquid comprises: The carbon quantum dots, furfuryl alcohol and water are mixed in a certain proportion to obtain the carbon quantum dots / furfuryl alcohol modified solution.

4. A method for preparing a carbon quantum dot optimized furfuryl alcohol modified material as claimed in claim 3, characterized in that: In the carbon quantum dot / furfuryl alcohol modified liquid, the concentration of the carbon quantum dots is 0.5-5%, the concentration of furfuryl alcohol is 10-70%, and the concentration of water is 25-89.5%, calculated by mass percentage.

5. The method for preparing a carbon quantum dot optimized furfuryl alcohol modified material according to claim 1, characterized in that: The procedure of the vacuum pressure impregnation method is to first perform vacuum treatment for 30 to 120 minutes at a vacuum degree of -0.05 to -0.1 MPa, then introduce the carbon quantum dots / furfuryl alcohol modification solution, and then perform pressure treatment for 60 to 180 minutes at a pressure of 0 to 2 MPa.

6. The method for preparing a carbon quantum dot optimized furfuryl alcohol modified material according to claim 1, characterized in that: The high temperature resistant and waterproof material is tin foil and / or silicone oil paper, and the room temperature aging time is 12 to 72 hours.

7. A method for preparing a furfuryl alcohol modified material based on carbon quantum dots optimization as claimed in claim 1, characterized in that: The heating curing procedure is to first treat at 60-80°C for 1-5 hours, then treat at 100-120°C for 5-24 hours, and finally remove the high temperature resistant waterproof material and dry at 40-80°C to constant weight.

8. A wood prepared by the method for preparing a carbon quantum dot optimized furfuryl alcohol modified material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparing method for environment-friendly resin reinforced flame-retardant modified wood

    CN107599086A

  • Method for improving wood performance based on synergistic effect of furfuryl alcohol / hyperbranched polymer

    CN118205060A

  • Ion-based carbon quantum dot and application thereof in resin curing

    CN118956387A

Cited By

  • Carbon-quantum-dot-optimized furfuryl-alcohol-modified wood and preparation method therefor

    WO2026148740A1